A cross-cultural investigation of design and visual preference of signage information from Hong Kong and Pakistan. (1st March 2021) - Iftikhar, Hassan; Asghar, Salman; Luximon, Yan
Abstract : Signage design has been considered critically important for wayfinding, being a functional medium of delivering environmental information. Complex institutional environments have several factors affecting the wayfinding, including but not limited to the design of information signage and its visual preference. Visual preferences of information design in wayfinding signage vary, depending on the cultural and individual differences. This study explores the variance in design and visual preferences of wayfinding signage and its influencing elements. Responses through online questionnaire have been accumulated by the participants from Hong Kong and Pakistan based on their design and visual preference of campus wayfinding signage. Questions were asked related to the user preferences for signage colour if in line with the institutional visual identity, mono or multi-colour coding of information and its visual volume. In total, 170 university students and visitors participated in the exploratory study from the respective countries. The results demonstrated that participants of Hong Kong preferred inline colours of signage, along with mono or less colour coding and detailed information. While the other group preferred attractive colours with multi-colour coding and less detailed wayfinding information with pictograms. Individual differences concerning age, literacy level and gender were also computed, however trivial differences have been recorded. This study suggests the need for detailed cross-cultural investigation concerning elements of signage design and visual preference to identify the drivers for culturally consistent university signage.